Age-Related Variation in Male Youth Athletes' Countermovement Jump After Plyometric Training: A Meta-Analysis of Controlled Trials. Issue 2 (February 2017) - Moran, Jason J.; Sandercock, Gavin R.H.; Ramírez-Campillo, Rodrigo; Meylan, César M.P.; Collison, Jay A.; Parry, Dave A.
Abstract : Abstract: Moran, J, Sandercock, GRH, Ramírez-Campillo, R, Meylan, CMP, Collison, J, and Parry, DA. Age-related variation in male youth athletes' countermovement jump after plyometric training: A meta-analysis of controlled trials. J Strength Cond Res 31(2): 552–565, 2017—Recent debate on the trainability of youths has focused on the existence of periods of accelerated adaptation to training. Accordingly, the purpose of this meta-analysis was to identify the age- and maturation-related pattern of adaptive responses to plyometric training in youth athletes. Thirty effect sizes were calculated from the data of 21 sources with studies qualifying based on the following criteria: (a) healthy male athletes who were engaged in organized sport; (b) groups of participants with a mean age between 10 and 18 years; and (c) plyometric-training intervention duration between 4 and 16 weeks. Standardized mean differences showed plyometric training to be moderately effective in increasing countermovement jump (CMJ) height (Effect size = 0.73 95% confidence interval: 0.47–0.99) across PRE-, MID-, and POST-peak height velocity groups. Adaptive responses were of greater magnitude between the mean ages of 10 and 12.99 years (PRE) (ES = 0.91 95% confidence interval: 0.47–1.36) and 16 and 18 years (POST) (ES = 1.02 [0.52–1.53]). The magnitude of adaptation to plyometric training between the mean ages of 13 and 15.99 years (MID) was lower (ES = 0.47 [0.16–0.77]), despite greater training exposure. Power performance as measured by CMJ may be mediated by biological maturation. Coaches could manipulate training volume and modality during periods of lowered response to maximize performance.